Development of a miniaturized stimulation device for electrical stimulation of cells - Xiong, Gordon Minru (2015)
Background: Directing cell behaviour using controllable, on-demand non-biochemical methods, such as electrical stimulation is an attractive area of research. While there exists much potential in exploring different modes of electrical stimulation and investigating a wider range of cellular phenomena that can arise from electrical stimulation, progress in this field has been slow. The reasons for this are that the stimulation techniques and customized setups utilized in past studies have not been standardized, and that current approaches to study such phenomena rely on low throughput platforms with restricted variability of waveform outputs.Results: Here, we first demonstrated how a variety of cellular responses can be elicited using different modes of DC and square waveform stimulation. Intracellular calcium levels were found to be elevated in the neuroblast cell line SH-SY5Y during stimulation with 5 V square waves and, stimulation with 150 mV/mm DC fields and 1.5 mA DC current resulted in polarization of protein kinase Akt in keratinocytes and elongation of endothelial cells, respectively. Next, a miniaturized stimulation device was developed with an integrated cell chamber array to output multiple discrete stimulation channels. A frequency dividing circuit implemented on the device provides a robust system to systematically study the effects of multiple output frequencies from a single input channel. Conclusion: We have shown the feasibility of directing cellular responses using various stimulation waveforms, and developed a modular stimulation device that allows for the investigation of multiple stimulation parameters, which previously had to be conducted with different discrete equipment or output channels. Such a device can potentially spur the development of other high throughput platforms for thorough investigation of electrical stimulation parameters on cellular responses.